Los inadaptados - Ureña, Jurgen, 1973-; Bagnarello, Johanna; Lobo, Tatiana (Producciones La Ventana, 2011)
The short film Los Inadaptados is an unusual journey through the streets of the Costa Rican capital from the eyes of Greta, Verónica, María José, Cristal and Tato. The film is a documentary whose story revolves around a group of transgender girls and the evolution of their lives. The plot focuses on the conflictive relationship between two characters, a "chapulín" (a criminal) and María José, a capital transvestite. --